The Rechtsstaat in Germany: a political idea and a legal principle (Discourse of Law and Administration, 2023)
Current discussions on the rule of law in the EU have at their heart the question of what rule of law means. In order to approach this conceptual question, it may be useful to distinguish the rule of law as a political idea from the requirements of the rule of law as a normative legal specification. This distinction is, at least, applicable for the German discussion on the Rechtsstaat. There is a political idea of the Rechtsstaat as an ideal of the state on the one hand, and a constitutionally specified legal principle, the Rechtsstaatsprinzip, in the German Grundgesetz on the other. The lines between the political and the legal concept are blurred, but they should be drawn with care.
Keywords: rule of law; Rechtsstaat; Rechtsstaatsprinzip; Grundgesetz; positivism